Adverse Events in Italian Nursing Homes During the COVID-19 Epidemic: A National Survey - Lombardo, Flavia L.; Salvi, Emanuela; Lacorte, Eleonora; Piscopo, Paola; Mayer, Flavia; Ancidoni, Antonio; Remoli, Giulia; Bellomo, Guido; Losito, Gilda; D’Ancona, Fortunato; Canevelli, Marco; Onder, Graziano; et al. (Frontiers in Psychiatry, 2020)
We performed a national survey on 3,292 nursing homes, either public or providing services both privately and within the national health system, out of the 3,417 nursing homes (NHs) covering the whole Italian territory. The list of NHs was provided by the Dementia Observatory, an online map of Italian services for people with dementia, which was one of the objectives of the implementation of the Italian National Dementia Plan. About 26% of residents in the Italian NHs for the older people listed within the Dementia Observatory site had dementia. The objective of our study was to report the frequency of adverse events that occurred during the months when SARS-CoV_2 spreading rate was at its highest in the Italian NHs and to identify which conditions and attributes were most associated with the occurrence of adverse events. Data are referred to 1,356 NHs that participated in the survey. Considering that 3,292 NHs were contacted, the overall response rate was 41.2% over a time-period of 6 weeks (from March 24 to May 5). About one third of the facilities (444 out of 1334) (33.3%) reported at least 1 adverse event, with a total of 2000 events. Among the included NHs, having a bed capacity higher than the median of 60 beds (OR=1.57, CI95% 1.17-2.09; p=0.002), an observed increased in the use of psychiatric drugs (OR=1.80, CI95% 1.05-3.07; p=0.032), adopting physical restraint measures (OR=1.97, CI95% 1.47-2.64; p<0.001), residents hospitalized due to with flu-like symptoms (OR =1.73, CI95% 1.28-2.32; p<0.001), and being located in specific geographic areas (OR=3.59, CI95% 1.81-7.08; OR = 2.90, CI95% 1.45-5.81 and OR = 4.02, CI05% 2.01-8.04 for, respectively, North-West, North-East and Centre vs South, p<0.001) were all factors positively associated to the occurrence of adverse events in the facility. Future recommendations for the management and care of residents in NH during the COVID-19 pandemic should include specific statements for the most vulnerable populations, such as people with dementia.